2021
DOI: 10.1007/s10546-021-00636-y
|View full text |Cite
|
Sign up to set email alerts
|

Sea-Spray-Generation Dependence on Wind and Wave Combinations: A Laboratory Study

Abstract: This paper investigates the effect of interacting winds and waves on the surface sea spray generation flux. To this end, the Marine Aerosol Tunnel Experiment (MATE2019) was conducted at the OSU-Pytheas large wind-wave tunnel facility at Luminy, Marseille (France), in June-July 2019.A unique range of air-sea boundary conditions was generated by configuring the laboratory with four types of wave forcing and five wind speeds ranging from 8 to 20 m s -1 . The configurations included both young and developed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 87 publications
3
40
0
Order By: Relevance
“…As the model of X21 is based on the wave steepness, considered the critical parameter in the generation of sea spray (e.g. Bruch et al., 2021), the model of X21 is preferred over that of Z06. This study considers, however, only one TC case which reached up to category 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the model of X21 is based on the wave steepness, considered the critical parameter in the generation of sea spray (e.g. Bruch et al., 2021), the model of X21 is preferred over that of Z06. This study considers, however, only one TC case which reached up to category 3.…”
Section: Discussionmentioning
confidence: 99%
“…This is because wave age provides information on the relative velocity of the dominant energetic wave with respect to the wind only, but not about the severity of the sea state, including wave breaking. The severity of the sea state is considered to be a major determinant of sea spray generation (e.g., Bruch et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This method, called the "profile method", is routinely used for wind parameter determination in this facility (see for example recent papers of [Villefer et al, 2021;Bruch et al, 2021] where vertical wind profiles are displayed with u * , z 0 , and U 10 determinations). Two examples of vertical wind profiles are plotted in Figure ( 5).…”
Section: Measurements 331 Wind Parametersmentioning
confidence: 99%
“…(2020) recently reported that air flow separation downstream of the wave crests increases with wind speed and wave slope. These airflow modifications are thought to have a significant impact on the droplet production in breaking waves and have previously been linked to surface features such as the significant wave height (Ovadnevaite et al., 2014), wave age (Laussac et al., 2018), and mean square slope (Bruch et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…(2018); Bruch et al. (2021)) knowledge and data on droplet velocity and acceleration statistics remain elusive in part due to the difficulty in performing such measurements.…”
Section: Introductionmentioning
confidence: 99%